Beginning iPhone and iPad Web Apps Scripting with HTML5, CSS3, and JavaScript - Apers, Chris; Paterson, Daniel (Apress : Imprint: Apress, 2010)
This book will help you join the thousands of successful iPhone apps developers without needing to learn Objective-C or the Cocoa touch APIs. If you want to apply your existing web development skills to iPhone and iPad development, then now you can. WebKit's support for HTML5 means any web developer can create compelling apps for both the iPhone and the larger-screen iPad. Beginning iPhone & iPad Web Apps takes you through the latest mobile web standards as well as the specific features of the iPhone and iPad. You'll learn about WebKit and Mobile Safari, HTML5 and CSS3, vector graphics and multimedia support. You'll discover the built-in hardware features of the iPhone and iPad and how best to take advantage of them. The market for web apps for the iPhone and iPad is expanding rapidly. You'll want to know about all the advantages, and Beginning iPhone & iPad Web Apps is the perfect starting point.